Young children's vacation experience: Through the eyes of parents. (January 2020) - Li, Mimi; Xu, Wenqing; Chen, Yuhao
Abstract: The travel industry has witnessed remarkable development of the children's market in recent decades; however, relevant academic research remains scarce, especially with younger children. By adopting a netnographic approach, this study explores young children's (0–4 years old) holiday experiences through the eyes of their parents. Research findings revealed parents' preferred types of destinations for family vacations. Two broad themes were identified from analyses of parents' accounts: enjoyment of nature and social development. Findings are discussed in the context of relevant literature, and industry recommendations are provided. Highlights: The study is one of the first attempts to explore the vacation experiences of children aged 0–4. Using data collected via netnography approach, detailed account of parents were analyzed. Two broad themes emerged from the analysis: enjoyment of nature and social development. The boundary between home environment and tourism destination is blurred for families traveling with young children. Children are active agent in the consumption of tourism space.